Volatility Spillovers and Correlation Between Cryptocurrencies and Asian Equity Market - Malhotra, Nidhi; Gupta, Saumya (International Journal of Economics and Financial Issues, 2019)
Although, the growth in the cryptocurrency market slowed down after the meteoric rise in late 2017, the market is still enjoying steady capital inflow. This has made the study of market dynamics between the cryptocurrencies and equity market indispensable. In this paper, the study of the volatility spillovers and correlation between the two has been undertaken by considering five Asian stock indices and four cryptocurrencies ranging from November 2014 to December 2018, to cover three phenomena- Leverage effect, Volatility spillovers and Time varying correlation using EGARCH, Diagonal BEKK and DCC tests respectively. Firstly, the EGARCH test reveals the absence of leverage effect in the returns of cryptocurrenices. Secondly, the multivariate GARCH test shows, out of all the cryptocurrencies taken, the past innovations in Bitcoin affect the future volatility of the equity market returns the most. Lastly, the DCC model reveals evidence of time varying correlation between the markets and Bitcoin. Keywords: Cryptocurrencies; Asian equity market; Volatility spillovers; Dynamic conditional correlation JEL Classifications: G12, G14, G17, C15, C32 DOI: https://doi.org/10.32479/ijefi.8624